Introduction: Community, Identity, Politics and Healthcare in Malaysia - Abdul Rahman Embong,; Chin Yee Whah, (Kajian Malaysia, 2011)
This special issue of Kajian Malaysia is concerned with "Community, identity, politics and healthcare" with a focus on Malaysia. It consists of 11 refereed articles, 7 of which were originally presented at the 7th International Malaysian Studies Conference (MSC7) organised by the Malaysian Studies Association at Universiti Sains Malaysia, Pulau Pinang in March 2010 while the other 4, though presented elsewhere, have also been included because of their relevance to the overall theme. The three sub-themes of this special issue, while seemingly unconnected, maybe linked to each other through both direct and indirect ways. Community and identity, as analytical constructs and empirical realities, are both of analytical value as well as of practical significance. As analytical constructs and empirical reality, both have become important foci of study and analysis. The community—be they a fishing community, an indigenous community, or other types of small-scale groups of people bound together by shared history, identity and interests including attachment to a locality—is often a site of struggle between the local with multifarious forces, including the various arms of the state and other vested interests. It is at the level of the community that we are able to capture processes of change, such as social mobility, as well as processes of empowerment and stakeholder participation in managing or controlling their lives including their environment